2023
DOI: 10.3390/diagnostics13152576
|View full text |Cite
|
Sign up to set email alerts
|

Human Parainfluenza Virus (HPIV) Detection in Hospitalized Children with Acute Respiratory Tract Infection in the Western Cape, South Africa during 2014–2022 Reveals a Shift in Dominance of HPIV 3 and 4 Infections

Jane Parsons,
Stephen Korsman,
Heidi Smuts
et al.

Abstract: The epidemiology of human parainfluenza viruses (HPIV), particularly its role as a cause of acute respiratory infection (ARI) in infants, has not been formally studied in South Africa. We evaluated HPIV prevalence in diagnostic samples from hospitalized children from public sector hospitals in the Western Cape between 2014 and 2022. HPIV infection was detected in 2–10% of patients, with the majority of infections detected in children less than 1 year of age. Prior to 2020, HPIV 4 (40%) and HPIV 3 (34%) were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
3
0
0
Order By: Relevance
“…The recent surge of ARIs in children within China has garnered international concern (9), epidemic trends of HPIVs were examined in this study. The current analysis found an overall HPIVs detection rate of 6.15% in ARIs and 5.40% in SARIs, aligning with the results of earlier research (10)(11). HPIVs ranked third among the most commonly identified respiratory pathogens, following HRSV and HRV.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The recent surge of ARIs in children within China has garnered international concern (9), epidemic trends of HPIVs were examined in this study. The current analysis found an overall HPIVs detection rate of 6.15% in ARIs and 5.40% in SARIs, aligning with the results of earlier research (10)(11). HPIVs ranked third among the most commonly identified respiratory pathogens, following HRSV and HRV.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that HPIVs predominantly infected children under five years old. However, HPIV2 was more frequently diagnosed in both children and adolescents, whereas HPIV4 was often detected in the elderly, confirming earlier reports ( 12 ). Furthermore, although HPIVs infections are known to cause a broad spectrum of clinical symptoms, certain serotype-specific manifestations such as fever, phlegm, and headache have been particularly associated with HPIV2 infections.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation